Factors Affecting the Treatment of Pulmonary TB in the Working Area of the Dungaliyo Health Center, Dungaliyo District, Gorontalo Regency - Cindrawaty Hasan; Fadly Syamsuddin; Hamna Vonny Lasanuddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
According to the WHO Global Tuberculosis Report for 2024, there will be around 10.8 million new TB cases worldwide in 2023, with an incidence of 134 cases per 100,000 population. Indonesia occupies the second position as the country with the most TB cases in the world. The purpose of this study is to find out the factors that affect the treatment of Pulmonary TB in the working area of the Dungaliyo Health Center in 2025. This study uses a quantitative method with a cross sectional study design, the sample in this study is Pulmonary TB patients who are treated at the Dungaliyo Health Center. Sampling was determined by a total sampling of 39 respondents. This research was conducted by interview method, the data collection tool is a questionnaire with a chi square test. From the results of this study, it can be concluded that 79.5% of respondents have lack of knowledge, 87.2% of respondents have strong motivation, 89.7% of respondents have an active PMO role. There was a relationship with knowledge (p = 0.037), there was a relationship with motivation (p = 0.038), there was a relationship with the role of PMO (p = 0.002), there was a relationship with income (p = 0.023) with the treatment of Pulmonary TB.Suggestion for the Dungaliyo Health Center is that PMO training should be held for family members who are PMO officers so that the treatment is complete. In addition, it also increases health promotion activities such as counseling, counseling, poster installation and distribution of leaflets about pulmonary TB disease.